Correlation of Endoscopic Findings with Meld Score in Patients with Cirrhosis - Noor, Abdurrehman Khan, Muhammad Tahir, Marya Hameed, Muhammad Siddique, Amna Ashraf, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Liver cirrhosis is reduced liver function caused by the growth of scar tissue known as fibrosis. The injury to hepatic tissues leads to the creation of scar tissue, which, over time, can replace normally functioning tissues. Objectives: The study evaluated the correlation of endoscopic findings with MELD and NIEC scores in patients with liver cirrhosis in Lahore. Methods: MELD scores were assessed based on the results of the biochemical laboratory tests using the equation. 9.57 x log(creatinine) + 3.7 x log(bilirubin) + 11.2 x log(INR) +6.43, while the endoscopy in assessing variceal characteristics was demonstrated according to the NIEC scoring system. Results: The etiological factors underlying the cirrhosis were hepatitis B (35.03%), hepatitis C (23.78%), Wilson disease (19.94%), autoimmune disorders (10.48%) and 3.58% with idiopathic etiology. The major clinical manifestations were jaundice (73.91%), followed by ascites (69.30%), gastrointestinal bleeding (34.27%), etc. The patients were classified as per the MELD scoring index into Group A (<18) and Group B (>18). The patients of Group A were significantly high 67.01% (262/391), (p<0.05) than Group B 32.99% (129/391) out of which 39 patients died. Endoscopic findings were also studied according to scoring at the NIEC index and the patients were classified into different risk assessment classes. Conclusion: Being a potentially life-threatening illness, cirrhosis necessitated prompt evaluation and action to minimize the death rate. In individuals with liver cirrhosis, NIEC and MELD scores appeared to be reliable predictors of esophageal varices. Keywords: Ascites; Endoscopy; Gastrointestinal bleeding; Icterus; Risk assessment.